Kentucky Bluegrass의 봄철 그린업을 위한 늦가을 칼륨 시비와 잔디피복재 적용시기 - 이상국(Sang-Kook Lee) (Weed & turfgrass science, 2021)
캔터키블루그래스 (Kentucky bluegrass, Poa pratensis)는 한지형 잔디의 한 종류이며, 성장을 위한 적정범위의 온도는18-24℃인 것으로 알려져 있다. 적정 온도범위보다 낮은 경우에는 저온피해로 인해 성장률이 감소하여 밀도가 낮아져, 잡초나 병의 발생, 토양 침식의 증가, 건조피해 증가등 여러가지 피해증상이 나타난다. 칼륨은 식물이 주변환경에 의해발생하는 저온피해와 같은 스트레스를 극복하는 능력을 향상시켜주는 원소로 잘 알려져 있다. 잔디피복재는 잔디가 저온피해에 노출 되었을때 관부를 보호하고, 지상부 회복에 도움을 주며, 겨울철 건조피해를 예방하는 방법으로 많이 사용이 되어 왔다. 본 연구는 잔디피복재의 적용시기와 늦가을 적용되는 칼륨의 시비량이 캔터키블루그래스의 봄철 그린업에 미치는 영향을 알아보기 위해 수행되었다. 총 4가지의 칼륨량 0, 5, 10, 20 g m-2 가 처리되었으며, 6가지 잔디피복재 적용시기인 무처리구, 매일처리구, 12, 1, 2, 3월이 처리되었다. 본 실험결과 칼륨의 잔디피복재와 상호작용은 나타나지 않았으며 칼륨의 효과에 대해서도 나타나지 않았다. 잔디피복재의 사용은 한지형잔디의 적정 생육온도 범위인 18- 24℃ 보다 낮을때 봄철그린업을 위한 잔디품질과 잔디피복률을 위해 최소 33일간의 적용기간이 필요했으며, 적용기간이 11일 이내이었을때는 무처리구와 차이점이 나타나지 않았다. 봄철그린업 기간에 높은 잔디품질과 잔디피복율이 요구되는 상황에는 잔디피복재의 적용시기가 12월, 1월, 2월일때 가장 높은 잔디품질과 잔디피복율이 나타났으며, 잔디피복재의 3월 적용은 무처리구 보다 나은 결과를 나타냈으나, 잔디피복재의 적용기간이 충분한 12, 1, 2월 처리구 보다낮은 잔디품질과 잔디피복율이 나타났다. 늦가을 칼륨의 시비효과는 잔디피복재 효과와 비교하여 봄철그린업에 대해의미있는 효과가 나타나지 않았으며, 일중 최고온도가 24.1℃ 그리고 19℃ 가 나타난 이후에는 모든 처리구에서 각각잔디피복률와 잔디품질에서 유의차가 나타나지 않았다. Kentucky bluegrass (Poa pratensis ), one of the cool-season grasses, has inappropriate growth when air temperature is lower than optimum range which are 18 to 24℃. It leads to sluggish growth, weed invasion, disease outbreak, and drought stress. Potassium (K) which is an essential nutrient for turfgrass growth is well-known to enhance turfgrass ability to tolerate environmental stresses such as low temperature stress. Turf cover has been used to protect the crowns from direct low temperatures and desiccation during the winter season. However, limited information has been reported on timing of the turf cover application and interaction with potassium application to improve cold tolerance. The objective of the study was to investigate the timing of turf cover application and late fall potassium application for Kentucky bluegrass spring green-up. The six timing of turf cover application which are no cover, daily, December, January, February, and March were treated. The four K rates which are 0, 5, 10, and 20 g m-2 were applied. The K application did not have effects on Kentucky bluegrass spring green-up. When air temperature is lower than 18℃, the effects of turf cover application is required for the period of 33 days for spring green up. If the period for cover application is less than 11 days, no effects of turf cover were found for turfgrass quality and coverage. When relatively high turf quality is required in the season of spring green up, the turf cover would be applied at the December, January, or February to ensure the enough period of turf cover application for increase spring green up. KCI Citation Count: 0